Wirausaha Cookies Brownies Sebagai Alternatif Peningkatan Kualitas Hidup Tuna Rungu - Widowati, Sri; Rofiah, Khofidotur; Firdausi, Yasmin (LPPPI Publishing, 2025)
Deaf individuals face barriers in accessing formal employment due to limitations in communication and training, making brownies cookie entrepreneurship a viable alternative to improve their quality of life. This study aims to examine how brownies cookie entrepreneurship can enhance the quality of life for deaf individuals. The research uses a qualitative case study approach with techniques including interviews, participatory observation, and documentation involving three deaf subjects who run a brownies cookie business. The results show that brownies cookie entrepreneurship has a positive impact on the quality of life of deaf individuals across various dimensions physical, psychological, social, and environmental. All three subjects experienced increased productivity and independence, along with improved self-confidence and social recognition. They were able to interact with their surroundings through social media and used their earnings to support personal and family needs. Supporting factors such as family support, disability communities, and social media strengthened the success of their businesses, although challenges remained in the form of communication barriers, limited capital, and lack of inclusive training opportunities.